Some issues and thoughts on the study of pure shale-type shale oil in the 7th Member of Yanchang Formation in Ordos Basin, China - Shutong Li; Shixiang Li; Jiangyan Liu; Mingyi Yang; Junlin Chen; Shan Zhang; Deyi Cui; Jiacheng Li (Journal of Natural Gas Geoscience, 2022)
The 7th Member of the Yanchang Formation (Chang 7 Member) in the Ordos Basin contains rich shale oil resources in which the exploration and development of the Chang 7 Member sandstone interbedded shale oil has made substantial breakthroughs. The exploration and development potential of the shale oil, an inevitableoil and gas replacement for Changqing Oilfield Company in the future, is immense. Its related geological basic research, however, is relatively weak. This paper provides elaborations and analyzation on basic science issue, including the characteristics of mud shale, the significance of shale oil exploration, the restoration of the formation of paleoenvironment, the organic matter enrichment effect of tuff, the catalysis of hydrocarbon generation, and more. It is presumed that enduring geological basic research, such as pure mud shale-type shale oil and modern lacustrine semi-deep lake-deep lake facies sedimentation investigations can provide valuable ideas and methods for the study of mud shale formation, paleoenvironment restoration, and formation mechanism. Meanwhile, we should pay close attention to research on the catalysis of tuff on the hydrocarbon generation of source rocks, and conduct a series of thermal simulation experiments on the catalysis of enriched elements in the tuff, which will provide important basic geological parameters for the exploration and development of Chang 7 Member pure mud shale-type shale oil.